Vitamin D Status and Usual Nutrient Intake of Filipino Children Aged 6–12 Years in Selected Areas in the Philippines: A 2018 National Nutrition Survey - Imelda Angeles-Agdeppa; Keith V. Tanda (Journal of Nutrition and Metabolism)
Background. This study aimed to determine the prevalence of vitamin D deficiency, usual nutrient intake, and food sources of vitamin D of Filipino children aged 6–12 years in selected areas in the Philippines. Methods. The National Nutrition Survey (NNS) collected blood samples of children aged 6–12 years from selected study sites: Manila City and Quezon City in the National Capital Region (NCR); Cagayan Province and Baguio City in Luzon; Northern Samar and Siquijor in Visayas; and Butuan City and Sultan Kudarat in Mindanao. About 789 children aged 6–12 years participated in this study. Serum vitamin D was determined by electrochemiluminescence binding assay (ECLIA). Food intake data were collected using two-day nonconsecutive 24 h food recall. Usual nutrient intakes were estimated using Personal Computer Software for Intake Distribution Estimation (PC-SIDE) program. Results. The mean serum vitamin D of 25 (OH)D was 72.7 ± 0.67 μmol/L. The overall prevalence of combined vitamin D deficiency (<50 μmol/L) and insufficiency (51–74 μmol/L) among children aged 6–12 years was 60.6%. Females had a higher prevalence of vitamin D insufficiency compared to males. NCR (57.9%) had a higher deficiency compared to the other areas. The usual intake of vitamin D (2 μg/day) among children was below the adequate intake of 5 μg/day. The main food sources of vitamin D are coming from fish (53%), pork (19%), and egg/egg dishes (16%). Conclusion. This study revealed that there is a significantly high level of vitamin D insufficiency in children aged 6–12 years. Filipino females had higher prevalence of vitamin D deficiency and insufficiency compared to males. Among the areas, NCR has the highest prevalence of deficiency/insufficiency.